2008
DOI: 10.1007/s11258-008-9543-6
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive success in the Mexican rewardless Oncidium cosymbephorum (Orchidaceae) facilitated by the oil-rewarding Malpighia glabra (Malpighiaceae)

Abstract: The pollination of one plant species can be facilitated by the presence of one or more neighboring plant species and evidence has been found in some rewardless species of orchid that benefit from the presence of rewarding plant species in the neighborhood. There are two pollination mechanisms by which a non-rewarding orchid attracts pollinators and increases its reproductive success: (1) A magnetic species effect that occurs even though the flowers do not resemble those of the other species, and (2) floral mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
2
22
0
4
Order By: Relevance
“…pollinator density [16] or the magnet-species effect [7,69]), further studies need to be carried out to investigate whether there is a general pattern of increased fitness in the presence of a rewarding model. Carmona-Díaz & García-Franco [32] reported higher levels of reproductive success in the Mexican species of Trichocentrum luridum (published as Trichocentrum cosymbephorum ) when occurring in sites where Malpighia glabra (Malpighiaceae) was abundant. This phenomenon was also observed in the deceptive orchid Disa nivea in South Africa and its Scrophulariaceae nectar-producing model, Zaluzianskya microsiphon [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pollinator density [16] or the magnet-species effect [7,69]), further studies need to be carried out to investigate whether there is a general pattern of increased fitness in the presence of a rewarding model. Carmona-Díaz & García-Franco [32] reported higher levels of reproductive success in the Mexican species of Trichocentrum luridum (published as Trichocentrum cosymbephorum ) when occurring in sites where Malpighia glabra (Malpighiaceae) was abundant. This phenomenon was also observed in the deceptive orchid Disa nivea in South Africa and its Scrophulariaceae nectar-producing model, Zaluzianskya microsiphon [21].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of deceitful orchids in the Mediterranean and Caribbean have concluded that this form of deception is more common than specifically mimicking a single model species [19]. Alternatively, some bee-blue-green Oncidiinae may be mimics of other malpig colour forms, as is thought to be the case between T. luridum and M. glabra [32]. …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the role of Malpighiaceae as model plants for most Oncidium ‐like orchids, as has been proposed many times (Van der Pijl & Dodson 1966; Nierenberg 1971; Van der Cingel 2001; Powell et al . 2003; Pemberton 2008; Renner & Schaeffer 2010), but scarcely documented (Carmona‐Díaz & García‐Franco 2009; Pemberton 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2003; Pansarin et al . 2008; Carmona‐Díaz & García‐Franco 2009). In other cases, a few species of orchids of the genus Oncidium and Tolumnia , pollinated by males of Centris bees, have been suggested to exploit the territoriality (Dodson & Frymire 1961; Van der Pijl & Dodson 1966; Nierenberg 1971) and mate‐seeking behaviors of these males bees (Dod 1976).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that the enlarged median sepal, incised lip, callus and stelidia of Oncidiinae evolved to mimick the shape of the petals and oil glands of rewarding flowers of Malpighiaceae (Figs. 2b–d and 3) in order to attract oil-collecting bees for pollination [35, 38, 40, 41].
Fig.
…”
Section: Introductionmentioning
confidence: 99%